Voltage Gated Sodium Channel Genes in Epilepsy: Mutations, Functional Studies, and Treatment Dimensions - Ademuwagun, Ibitayo Abigail; Rotimi, Solomon Oladapo; Syrbe, Steffen; Ajamma, Yvonne Ukamaka; Adebiyi, Ezekiel (Frontiers in Neurology, 2021)
Genetic epilepsy occurs as a result of mutations in either a single gene or an interplay of different genes. These mutations have been detected in ion channel and non-ion channel genes. A noteworthy class of ion channel genes are the voltage gated sodium channels (VGSCs) that play key roles in the depolarization phase of action potentials in neurons. Of huge significance are SCN1A, SCN1B, SCN2A, SCN3A and SCN8A genes that are highly expressed in the brain. Genomic studies have revealed inherited and de novo mutations in sodium channels that are linked to different forms of epilepsies. Due to the high frequency of sodium channel mutations in epilepsy, this review discusses the pathogenic mutations in the sodium channel genes that lead to epilepsy. In addition, it explores the functional studies on some known mutations and the clinical significance of VGSC mutations in the medical management of epilepsy. The understanding of these channel mutations may serve as a strong guide in making effective treatment decisions in patient management.